On Intensive Endophoric Devices in English - Krivochen, Diego (Studia Anglica Posnaniensia, 2019)
This paper deals with the syntactic and semantic properties of a specific kind of anaphoric device (AD) in English, instantiated by Prn+SELF lexical items (himself/herself/itself…; ‘SELF’ henceforth), which do not behave like anaphors in the sense of Binding Theory either syntactically or semantically. These devices have received the name of intensives in the grammatical literature (Leskosky 1972; Siemund 2000, among many others). We will look at the syntactic behaviour of so-called intensives in different syntactic contexts, and refine the classification of these ADs taking into consideration (a) how each type of intensive is derived, (b) the kinds of syntactic rules that can affect them, and (c) their meaning.